Utilization of Home Yard Land With Vegetable Cultivation to Improve Family Economy - Chrismesi Pagiu; Rati Pundissing; Dian Tangke Allo; Dwibin Kannapadang; Yohanis Lotong (Manunggal Halim Jaya, 2022)
The service seeks to promote knowledge, skills, and awareness and encourage each household in the village of Ratte Kurra to use home yard land to better the family's economic situation and adopt simple planting and maintenance that the community may easily implement. The implementation strategy employs extension approaches and is immediately followed by cultivating vegetable crops and a study of the extension's results. After this activity, there was a significant change in the function of the yard; the community grasped the value of using the home yard for vegetable production and income management by selling crops to better the family's economic situation.